The reform by Law No. 31699 of the appeal in cassation regulated by New Labor Procedure Law - Arévalo Vela, Javier (2023)
The appeal in cassation is an important legal institution of procedural law; in labor matters is regulated by the New Labor Procedure Law, Law No. 29497 and by Law No. 31699, Law that Optimizes the Appeal in Cassation. Using hermeneutic method, an analysis is made reflecting on the purposes of cassation as an institution of procedural law. It is also specified that the Supreme Court of Justice of the Republic has powers that allow it to decide the cases in which it will rule.